2016
DOI: 10.1002/jbm.b.33662
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide cross‐linked UHMWPE blended with vitamin E

Abstract: Radiation crosslinked ultrahigh molecular weight polyethylene (UHMWPE) is the bearing surface material most commonly used in total joint arthroplasty because of its excellent wear resistance. Crosslinking agents such as peroxides can also effectively increase wear resistance but peroxide crosslinked UHMWPE has low oxidative stability. We hypothesized that the addition of an antioxidant to peroxide crosslinked UHMWPE could improve its oxidation resistance and result in mechanical, tribological, and oxidative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…This is presumably due to increased penetration depth of peroxide with increased temperature during doping. In further analysis, the mechanical testing of surface cross‐linked UHMWPE using diffusion of emulsified peroxides similar to what was shown here corroborated improved toughness compared to uniformly cross‐linked UHMWPEs …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is presumably due to increased penetration depth of peroxide with increased temperature during doping. In further analysis, the mechanical testing of surface cross‐linked UHMWPE using diffusion of emulsified peroxides similar to what was shown here corroborated improved toughness compared to uniformly cross‐linked UHMWPEs …”
Section: Discussionsupporting
confidence: 77%
“…Recently, techniques have been developed to improve the oxidation resistance of cross‐linked UHMWPEs by the incorporation of antioxidants, especially blending with the natural antioxidant vitamin E . The blending of vitamin E in peroxide cross‐linked UHMWPE was shown to improve the oxidation resistance of peroxide cross‐linked UHMWPE . In addition, higher concentrations of vitamin E could be used when using peroxide cross‐linking than when using radiation cross‐linking because peroxide cross‐linking was less sensitive to vitamin E as a free radical scavenger.…”
mentioning
confidence: 99%
“…The hindrance of cross‐linking in UHMWPE by the antioxidant vitamin E and the changes in related properties have been well documented in vitamin E‐blended, consolidated and radiation cross‐linked UHMWPE . It was also suggested that peroxide cross‐linking of UHMWPE may be less sensitive to the presence of vitamin E, thus enabling the use of higher concentrations of vitamin E in the blended UHMWPE. The target cross‐link density of approximately 260 mol/m 3 , which was the measured cross‐link density of 100‐kGy irradiated and melted highly cross‐linked control UHMWPE without any additives, was reached at 0.57 wt% peroxide for a 0.2 wt% vitamin E blend and at 0.79 wt% peroxide for a 0.5 wt% blend (intrapolated form the data presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of vitamin E also enabled peroxide cross‐linking of UHMWPE preventing oxidation during consolidation and cross‐linking. The addition of vitamin‐E also imparted excellent oxidative stability in finished articles . We recently introduced high temperature melting as a method to improve the fatigue toughness of cross‐linked UHMWPEs and advanced the application of this method to peroxide crosslinking of UHMWPE/vitamin‐E blends.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical cross‐linking of UHMWPE blended with the organic peroxide 2,5‐Di ( tert ‐butylperoxy)‐2,5‐dimethyl‐3‐hexyne (P130) is optimal above 180°C, at which temperature the half‐life of P130 dissociation is around 1 min. This is possibly a reason why P130 cross‐linking of UHMWPE is less sensitive to the presence of vitamin E, enabling incorporation of a higher concentration of the antioxidant than that used with radiation cross‐linking . For example, while a 1 wt % vitamin E blended UHMWPE has a cross‐link density equivalent to conventional gamma sterilized UHMWPE when irradiated to 200 kGy, it can have a cross‐link density equivalent to that of a highly cross‐linked UHMWPE when cross‐linked using 1 wt % peroxide.…”
Section: Introductionmentioning
confidence: 99%